The Effect of Group Counseling Services with Reframing Techniques on the Reduction of Physical Aggressive Behavior in Adolescents - Rizka Aulia Yanda; Alfin Siregar (Universitas Muhammadiyah Enrekang, 2024)
This research aims to see whether the refaming method combined with group counseling services can have an effect on reducing physically aggressive behavior in adolescents. This research uses a quantitative approach with a pre-experimental research design. The samples taken in this research were 10 students in class VIII of SMP Negeri 1 Serbajadi using purposive sampling technique. Data collection used in this research was through observation, interviews and questionnaires. The data analysis used in this research is the paired sample t-test, where this test shows the difference in the average before and after treatment is given. Based on research findings, Group Counseling Services have a significant effect on adolescents; The t-count result of 3.691 exceeds the t-table value by 5%, namely 1.812. Before the existence of group counseling services, findings on the development of aggressive behavior showed that 30% of 3 children had very good aggressive behavior and 70% of 7 teenagers had moderate violent behavior. After the group counseling session, research findings revealed developments that showed that 10 children showed 100% good aggressive behavior. So group counseling services with this reframing technique can be used by future researchers to help reduce physically aggressive behavior in teenagers.